ANALISIS YURIDIS JUDI ONLINE DALAM PERSPEKTIF HUKUM PIDANA ISLAM DAN HUKUM PIDANA POSITIF DI INDONESIA - NIM. A1011171022, HERI SURAHMAN (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractOnline gambling is a form of crime that arises due to the misuse of technology, at this time online gambling is a very worrying crime because of inadequate law enforcement, in Indonesia online gambling is regulated in Article 27 Paragraph (2) of the generally accepted ITE Law. for all regions in Indonesia, but in the province of Aceh, the government there has special authority to regulate its area using Islamic law. This shows that Islamic law is part of the law that lives in society.The purpose of this study is to understand the views of online gambling according to Islamic Law and National Criminal Law, which then aims to foster a critical attitude towards a criminal act, especially the crime of online gambling and is also useful as a reference in future legal reforms.The results of this study indicate that the regulation of online gambling carried out by the Indonesian state has a dominance of similarities in the form of regulation and also the elements of online gambling, and also online gambling according to each of these views shows different views in the phrase